Sistem Monitoring Ph Air Kolam Ikan Lele Menggunakan Sensor Bgt-D718-Ph dan PLC Outseal Berbasis Internet of Things - Mubarak, Rifqi; Zarory, Hilman; Ullah, Aulia; Faizal, Ahmad (Building of Informatics, Technology and Science (BITS), 2024)
Catfish farming is one of the choices for communities to meet the need for animal protein and also contributes to the development of the fisheries sector. High demand from consumers in various regions in Indonesia makes the opportunity for catfish farming very promising. Water quality plays an important role in the success of catfish farming, especially pH fluctuations that can affect the health and growth of fish. In an effort to monitor and regulate pH values effectively, the development of a system using Internet of Things (IoT) technology has been carried out. This system allows real-time monitoring of water pH in catfish ponds remotely through the Blynk application. Additionally, this research also includes the design and development of a measuring device using IoT technology based on ESP8266 to monitor catfish pond pH in real-time without physical presence at the location. This device not only provides real-time data display for decision-making considerations but also offers efficiency in time usage. The aim of this research is to develop a real-time water pH monitoring system for catfish ponds at Fardu Farm Pekanbaru, which utilizes the BGT-D718-PH RS-485 sensor and PLC Outseal mega v3 for data processing, as well as communication with the Blynk application through ESP 8266 as the IoT-based HMI. In this study, testing was conducted over a period of 14 days by comparing the readings of the measuring instrument with those of the sensor, resulting in an error of 0.04. Throughout the testing period, the pH levels in the catfish pond fluctuated due to varying weather conditions, ranging from rainy to hot weather. The testing was conducted under two conditions: normal pH and problematic pH. From these tests, it can be concluded that the water pH monitoring system has been successfully developed. Consequently, this system can serve as an effective solution for catfish farmers to monitor pH conditions without the need to be physically present at the location